Successful pregnancy and delivery outcome after the surgical treatment of pituitary adenoma in the first trimester of pregnancy (a clinical case) - O.V. Barakina; T.N. Markova; S.G. Ismailova; I.M. Godkov; V.M. Grabovskiy; P.V. Kozlov (LCC «Medicine-Inform», 2022)
O.V. Barakina1, T.N. Markova1,2, S.G. Ismailova1, I.M. Godkov3,4, V.M. Grabovsky1, P.V. Kozlov4 1City Clinical Hospital No. 52, Moscow, Russian Federation 2A.I. Yevdokimov Moscow State University of Medicine and Dentistry, Moscow, Russian Federation 3Moscow Multi-profile Clinical Center "Kommunarka," Moscow, Russian Federation 4Pirogov Russian National Research Medical University, Moscow, Russian Federation The authors present a clinical case of partial hypopituitarism developed in a 31-year-old patient during the first trimester of pregnancy after the surgical treatment of hemorrhagic pituitary adenoma. The onset of the diseases was recorded on the 12th week of pregnancy and was characterized by such specific clinical manifestations as severe headache, multiple spells of vomiting, diplopia and right-sided ptosis. The contrast-enhanced MRI revealed a pituitary adenoma with a "fresh" hemorrhage and the destruction of anterior wall and floor of the sella turcica, and the invasion into the sphenoid and right cavernous sinuses. The patient underwent emergency surgery - the endoscopic endonasal approach for total resection of pituitary adenoma. Hypopituitarism manifestations identified in the postoperative period were relieved by hormone replacement therapy. A timely diagnosis and prompt decision on the surgical treatment of pituitary adenoma, as well as a multidisciplinary team approach to patient care ensured the appropriate management of the underlying disease, successful pregnancy, childbirth outcome and high maternal quality of life. Keywords: pituitary adenoma, pregnancy, management practices, hemorrhage, pituitary apoplexy, hypopituitarism, surgical treatment. For citation: Barakina O.V., Markova T.N., Ismailova S.G. et al. Successful pregnancy and delivery outcome after the surgical treatment of pituitary adenoma in the first trimester of pregnancy (a clinical case). Russian Journal of Woman and Child Health. 2022;5(4):326-331 (in Russ.). DOI: 10.32364/2618-8430-2022-5-4-326-331.